2011
DOI: 10.1088/0004-637x/734/2/75
|View full text |Cite
|
Sign up to set email alerts
|

X-RAY WARM ABSORPTION AND EMISSION IN THE POLAR-SCATTERED SEYFERT 1 GALAXY Mrk 704

Abstract: We present a detailed study of the ionized environment of the Seyfert 1 galaxy Mrk 704 using medium-and high-resolution X-ray spectra obtained with a long XMM-Newton observation. The 0.3-10 keV continuum, well described by a power law (Γ ≈ 1.86) and two blackbodies (kT ≈ 0.085 and 0.22 keV), is found to be affected by a neutral partial covering absorption (N H ≈ 10 23 cm −2 , covering fraction ≈0.22) and two warm absorber components. We identify a low-ionization, ξ ∼ 20 erg cm s −1 , and high outflow velocity,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 44 publications
3
17
0
Order By: Relevance
“…Polar-scattered Sy1s, including Mrk 1239, often show significant absorption features in the X-ray band, which is in agreement with the picture that our LOS passes close to their torus opening angles (e.g. Jiménez-Bailón et al 2008;Piconcelli et al 2013;Laha et al 2011;Newman et al 2021). For instance, the polar-scattered Sy1 Mrk 704 shows not only a partial covering neutral absorber with H ≈ 10 23 cm −2 and Cfact=0.22 but also two layers of warm absorbers that are associated with the broad line region (Laha et al 2011).…”
Section: Comparison With Other Polar-scattered Sy1ssupporting
confidence: 90%
“…Polar-scattered Sy1s, including Mrk 1239, often show significant absorption features in the X-ray band, which is in agreement with the picture that our LOS passes close to their torus opening angles (e.g. Jiménez-Bailón et al 2008;Piconcelli et al 2013;Laha et al 2011;Newman et al 2021). For instance, the polar-scattered Sy1 Mrk 704 shows not only a partial covering neutral absorber with H ≈ 10 23 cm −2 and Cfact=0.22 but also two layers of warm absorbers that are associated with the broad line region (Laha et al 2011).…”
Section: Comparison With Other Polar-scattered Sy1ssupporting
confidence: 90%
“…• Mrk 704- Laha et al (2011) have found two discrete WA components with ξ ∼ 20 and ξ ∼ 500. Both these ionisation states and the ouflow velocities are comparable with our detections.…”
Section: Warm Aborbers In X-rays 41mentioning
confidence: 99%
“…In our analysis we detect an additional component of WA with log ξ ∼ 3.13. Laha et al (2011) had detected a partially covering neutral absorber.…”
Section: Warm Aborbers In X-rays 41mentioning
confidence: 99%
“…During the revision of the present work, we became aware of a paper by Laha et al (2011) dealing with the analysis of the second XMM-Newton observation of Mrk 704. The results of their analysis are qualitatively similar to ours, the quantitative differences probably mostly related to the somewhat different spectral model adopted 3 .…”
Section: The Second Observationmentioning
confidence: 99%